â€œKompetensiâ€ Sebagai Landasan Konseptual Kebijakan Kurikulum Sekolah di Indonesia - Hermana Somantrie (Jurnal Pendidikan dan Kebudayaan, 2010)
The concept of â€œcompetencyâ€ has been applied in schoolâ€™s curriculum in Indonesia in the early of twenty-first century. Competency includes knowledge, attitude, and skills. The integration of competency through curriculum has given a new perspective in education world of Indonesia. Such curriculum is labelle specifically as â€œCompetency-Based Curriculumâ€ or (in Bahasa Indonesia) is â€œKurikulum Berbasis Kompetensiâ€. Traditionally, curriculum has always been labelled by the year of its promulgation. For example, the 1975 Curriculum was promulgated in 1975. This kind of curriculum labelling was also applied to the 1984 Curriculum and the 1994 Curriculum.Â ABSTRAKKonsep kompetensi telah digunakan dalam kurikulum sekolah di Indonesia pada awal abad ke-21. Kompetensi mencakup pengetahuan, sikap, dan keterampilan. Integrasi kompetensi melalui kurikulum telah memberikan perspektif baru dalam pendidikan di Indonesia. Kurikulum semacam ini dinamakan dengan dengan Kurikulum Berbasis Kompetensi. Secara tradisional, kurikulum di Indonesia diberikan label sesuai dengan tahun pemberlakuannya, seperti Kurikulum 1975 diberlakukan tahun 1975, begitu pula Kurikulum 1994 dan Kurikulum 2004.